Reverse Design of Cycloid Tooth Profile Without Trapped Oil and Implementation Measures of Low Flow Ripple for Gear Pump - Yuncai Xia; Haibin Hao; Yin Mao (Jixie chuandong)
In order to solve the two structural problems of trapped oil and large flow ripple in gear pump and based on transmission advantages of cycloid gear and its forming principle，tooth number and radius factor of rolling circle which can best reflect pump performance are taken as structural parameters of cycloidal tooth profile，central angle，radius factor and pressure angle of addendum arc functional parameters of gear pump，a cycloid tooth profile with a contact ratio of 1 is constructed in a reverse way and the structural problem of large flow ripple of original single gear pair is solved by the construction of double gear pairs and minimization of ripple coefficient. All results show that the reverse design method of cycloidal tooth profile is simple and accurate，and can be directly used by general engineers； the contact ratio of a single gear pair is 1 to ensure that gear pump has no trapped oil phenomenon； the axial dislocation assembly of double gear pairs with special angle of π divided by tooth number is easy to be realized，and axial comprehensive contact ratio is 2 to ensure transmission stability of cycloidal gear pair； minimum number of teeth is 6 and there is no root cutting phenomenon； compared with single gear pair，an about 75% ripple improvement rate is seen in double gear pair and the optimal tooth profile parameters based on the minimization of ripple factor can be directly applied to the production practice，etc. The aim is to provide a theoretical basis for further research and development of low flow ripple gear pump without trapped oil.